Economies of size in national agricultural research systems - Fuglie, Keith O.; Rada, Nicholas (International Food Policy Research Institute, 2016)
This chapter expands on Fuglie and Rada (2013) by examining size efficiencies in the economic returns to national agricultural research in SSA. The approach is to empirically estimate how past investments in NARSs affected agricultural productivity in SSA counties, and to examine whether there are systematic differences in the rates of return to agricultural research and development (R&D) among small, midsize, and large countries. In this context, national agricultural research spending is treated as an investment in “knowledge capital.” However, because of the length of time required for research investments to generate the technologies farmers ultimately adopt, these long-lasting impacts accrue with a time lag.